ATLETISMO (AINDA) NÃO SE APRENDE NA ESCOLA? REVISITANDO ARTIGOS PUBLICADOS EM PERIÓDICOS CIENTÍFICOS DA EDUCAÇÃO FÍSICA NOS ÚLTIMOS ANOS - Eduardo Vinícius Mota e Silva; Florence Rosana Faganello Gemente; Guy Ginciene; Juliana Cardoso Daniel; Sara Quenzer Matthiesen (Universidade Federal do Rio Grande do Sul, 2015)
Based on a survey in scientific journals, this study aimed to verify the actual presence of athletics in Physical Education classes. We used a systematic review of articles published between 2005 and 2013 in 15 PE journals. The articles verified come from distinct states and cities in Brazil. Interviews and questionnaires were used to collect data from Physical Education teachers and undergraduate students. The results show an increase in the presence of athletics in school Physical Education classes.